Technological Progress and Physical Activity - Milić, Zoran; Jakovljević, Nebojša; Hilčenko, Slavoljub (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
The time in which we live is called the time of the information revolution and is characterized by a high degree of industrialization, technical progress and automation, which results in a reduction in physical activity, i.e. volume of daily movement activities. Thus, man relies more and more on his intellectual abilities, and less and less on movement. It is for this reason that a person should dedicate himself to daily moderate physical exercise in order to compensate for his daily need for movement. Proper attitude towards physical exercise, as well as the formed habit of exercising in early childhood, are some of the crucial factors that determine whether physical activity in the later stages of life will be an integrated part of life. Only in this way can today’s man avoid the consequences of hypokinetic syndrome.
Keywords: physical activity; industrial progress; hypokinesia; technological progress